Hematological and Hormonal Effects of Spirulina Platensis Algae Powder and Zinc Sulfate on Iraqi Local Goats During Late Pregnancy (Texas Journal of Agriculture and Biological Sciences, 2023)
The motive of this study to investigate the impact of Spirulina Platensis algae powder and zinc sulphate on some haematological and hormonal parameters of female Iraqi- Local goats. 20 female goats were used, aged 2-3 years, average weight of 30.79 ± 0.47, divided randomly (n=5) into four groups. Group1 did not receive any supplements (control group), Group2 (Zn) received (50 mg zinc/kg diet), Group3 (SP) received (5g spirulina/kg diet), Group4 (Zn+Sp) received combined of zinc (50 mg/kg diet) and spirulina (5g/kg diet). The trial period was 180 days. The results indicated that (Sp) and (Zn+Sp) groups significantly (P ≤ 0.05) superior in RBC, Hb, Hct, and significantly decreased (P ≤ 0.05) the percentage of neutrophil cells in all treated groups compared to control. And a significant decrease (P ≤ 0.05) of insulin level in the Sp and Zn+Sp treatments, with an improvement in insulin resistance in all treated animals compared to the control group, with a rise of T4 hormone in Zn and Zn+Sp groups and an increase of T3 in Goats that treated with Zn+Sp supplements. Generally, combination of spirulina platensis algae powder and zinc sulphate can be used to enhance physiological performance of field animals.